Regular Physical Activity and Life Satisfaction: Unpacking the Roles of Self-Control and Emotion Regulation - Wiktor Potoczny; Radosława Herzog-Krzywoszańska; Łukasz Krzywoszański (Applied Sciences)
Physical activity is an essential component of a healthy lifestyle. Regular exercise and physical activity have many benefits for both the body and mind. This study examined the possible mediating effects of self-control and forms of emotion regulation on life satisfaction. A total of 186 adults participated in an online survey. Subjects answered questions regarding the regularity of participation in various forms of physical activity and completed questionnaires assessing self-control, emotional regulation, and life satisfaction. The Satisfaction with Life Scale and the Brief Self-Control Scale were used to assess life satisfaction and dispositional self-control. The Emotion Regulation Questionnaire was used to measure two different forms of emotion regulation: cognitive reappraisal and expressive suppression. Based on self-reported average minutes spent exercising per week, participants were classified into four levels of physical activity according to World Health Organization guidelines. The mediation analysis results showed that dispositional self-control and cognitive reappraisal fully mediated the relationship between physical activity level and life satisfaction. This suggests that regular physical activity may increase levels of self-control and cognitive reappraisal, which in turn leads to greater life satisfaction. These findings highlight the importance of regular exercise in promoting well-being and increasing life satisfaction through its beneficial effects on self-control and emotion regulation.